Task repetition and collaborative writing by EFL children: Beyond CAF measures - Hidalgo, María Ángeles; Lázaro-Ibarrola, Amparo (Studies in Second Language Learning and Teaching, 2020)
Research into the potential of collaborative writing is relatively new. Similarly, task repetition (TR), which has been claimed to be a valuable tool for language learning, has been rarely explored in the context of writing. Therefore, little is known about the potential of combining TR and collaborative writing, and even less if we focus on young learners (YLs), who constitute a generally under-researched population. With these research gaps in mind, the present study examines the compositions of 10 pairs of learners of English as a foreign language (EFL) (aged 12) who write the same text in response to the same picture prompt three times over a three-week period. Our analysis includes the language-related episodes (LREs) that learners generate while writing collaboratively and, also, a thorough analysis of the three drafts that students produce, including quantitative (complexity, accuracy and fluency (CAF)) and holistic measures. Results show that learners’ compositions improve with repetition when measured by holistic ratings although CAF measures fail to grasp this improvement. As for the LREs, a great amount was found, most of the episodes were focused on form, most were successfully resolved and their amount declined with TR. In light of these results we argue in favor of the inclusion of holistic measures when analyzing students’ productions and discuss the positive effects of collaborative writing in the context of TR with YLs.